La temporalidad Diegética en la novela Cien Años de Soledad de Gabriel García Márquez - Chávez Pozo, Juliana Gisela (2018)
In this research work entitled: "The diegetic temporality in the novel one hundred years of solitude by Gabriel García Márquez", its objective is to analyze the events of the diegesis in the novel through the theory of order proposed by Gérard Genette._x000D_ _x000D_ The order of disposition of the events or temporal segments in the narrative discourse has been studied with the order of succession of those same events or temporal segments in history, to the extent that it is explicitly indicated by the story itself or can be inferred from such or indirect indication._x000D_ _x000D_ In short, this research work confirms the existence of anachronisms that adequately explain the functioning of temporality from the point of view of narratology. Also, that report becomes a reference for literary research for other similar works.